2000
DOI: 10.1002/1099-128x(200005/06)14:3<171::aid-cem591>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Application of PARAFAC for calibration with excitation-emission matrix fluorescence spectra of three classes of environmental pollutants

Abstract: Parallel factor analysis (PARAFAC) is applied to three calibrations of a field‐portable, cuvette‐based, single‐measurement, excitation–emission matrix fluorometer. In the first example the fluorometer is calibrated based on interactions between a non‐fluorescent DDT‐type pesticide and a fluorescent dye. PARAFAC is employed to deconvolve the fluorescence profiles of dissociated and complexed dye states. Calibration is performed based on the intensity of dye–pesticide fluorescence. In the second example, weighte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…It was shown that tryptophan and tyrosine and also high molecular weight Maillard reaction polymers and polyphenolic compounds were important fluorophores. In an investigation of the interactions between a nonfluorescent DDT-type pesticide and a fluorescent dye, PARAFAC was employed to find the fluorescence profiles of complexed dye states [9]. Furthermore, the ability to quantify trace pesticides and polycyclic aromatic hydrocarbons by fluorescence spectroscopy and PARAFAC modeling was investigated by Jiji et al [10].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that tryptophan and tyrosine and also high molecular weight Maillard reaction polymers and polyphenolic compounds were important fluorophores. In an investigation of the interactions between a nonfluorescent DDT-type pesticide and a fluorescent dye, PARAFAC was employed to find the fluorescence profiles of complexed dye states [9]. Furthermore, the ability to quantify trace pesticides and polycyclic aromatic hydrocarbons by fluorescence spectroscopy and PARAFAC modeling was investigated by Jiji et al [10].…”
Section: Introductionmentioning
confidence: 99%
“…The PARAFAC algorithm proposed by Harshman 34 is a representative method of the third group. These have successfully solved many practical problems, such as environmental monitoring, 41 the analysis of biological samples, 42,43 and the quantitation of drugs. 44 Several algorithms 18,25,[35][36][37][38][39][40] proposed recently were compared by Faber et al 45 Their results showed that the developments of three-way data analysis and second-order calibration are still indispensable.…”
Section: 14mentioning
confidence: 99%
“…Fluorescence excitation-emission data are utilized in the fields of medicine [1] and analytical chemistry [2], as well as for scientific studies focused on the environment [3], defense/security [4], and energy [5]. Specifically relating to energy research, Sandia has recently begun an effort to characterize the fluorescence signatures of bulk algal samples for assessment of both local and remote approaches for appraisal of algal health for biofuel production [6].…”
Section: Introductionmentioning
confidence: 99%